2018
DOI: 10.1029/2018ja025229
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of the Energy and Flux Morphology in an Aurora Observed at Midlatitude Using Multispectral Imaging

Abstract: Energies and fluxes of precipitating electrons in an aurora over Lowell, MA on 22-23 June 2015 were derived based on simultaneous, high-resolution (≈ 0.02 nm) brightness measurements of N + 2 (427.8 nm, blue line), OI (557.7 nm, green line), and OI (630.0 nm, red line) emissions. The electron energies and energy fluxes as a function of time and look direction were derived by nonlinear minimization of model predictions with respect to the measurements. Three different methods were compared; in the first two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The NeI 630.5‐nm line (present in street lights) was used as an indicator of cloud activity as reflection of street lights from clouds acts as a proxy for sky conditions. See Aryal et al () for a more detailed description of the spectra extraction procedure for HiT&MIS.…”
Section: Measurementsmentioning
confidence: 99%
“…The NeI 630.5‐nm line (present in street lights) was used as an indicator of cloud activity as reflection of street lights from clouds acts as a proxy for sky conditions. See Aryal et al () for a more detailed description of the spectra extraction procedure for HiT&MIS.…”
Section: Measurementsmentioning
confidence: 99%
“…The red aurora usually occurs in a height range of 200∼400 km (Aryal et al., 2018; He et al., 2020, 2021). The maximum visible region from the ancient observatory in Seoul, Korea for this height range is shown as the cyan and pink circles respectively in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this study supports earlier studies that found pulsating auroras have a narrower luminous layer in comparison with other auroral phenomena (Brown et al., 1976; Kataoka et al., 2013). To validate the vertical thickness and height of aurora based on our model calculation of spatial extent of flash aurora, we will combine both auroral tomography techniques for three‐dimensional optical structures (Tanaka et al., 2011) and estimation techniques about characteristic energies using optical emissions (Aryal et al., 2018; Grubbs et al., 2018), in future studies. Our calculations can be used to resolve this long‐standing issue about the vertical thickness of pulsating auroras, because our model can estimate both four‐dimensional (three‐dimensional space and time) auroral evolutions and characteristic energy based on the cyclotron resonance with chorus wave propagation.…”
Section: Effects Of Chorus Wave Propagationmentioning
confidence: 99%